Attachment anxiety in young adulthood is associated with childhood unpredictability and predicts intentions to engage in unprotected sex. (1st June 2020) - French, Juliana E.; Whitley, Katherine A.; Altgelt, Emma E.; Meltzer, Andrea L
Highlights: Childhood unpredictability was associated with attachment anxiety in young adults. Unpredictability was indirectly associated with intentions to have unprotected sex. Attachment anxiety (but not avoidance) mediated this indirect association. Results were unique to intentions to have sex without protection against pregnancy. Results did not extend to intentions to have sex without protection again STDs. Abstract: Developing a better understanding of the individual differences associated with people's intentions to engage in unprotected sex is crucial to reducing rates of unplanned pregnancy and the spread of sexually transmitted diseases (STDs) among young adults. We thus used a sample of young adults in the U.S. to examine the extent to which two notable individual differences—romantic attachment insecurity and childhood ecology—account for variability in people's intentions to engage in unprotected sex. Individuals with more (versus less) unpredictable childhood ecologies demonstrated greater attachment anxiety in early adulthood that was associated with stronger intentions to engage in sex without protection against pregnancy (but not against STDs). In contrast, harsh childhood ecologies were unassociated with attachment insecurity and intentions to engage in unprotected sex. We discuss implications and future research directions.